Age-Sensitive Design of Online Health Information: Comparative Usability Study - Pak, Richard; Price, Margaux M; Thatcher, Jason (JMIR Publications, 2009)
BackgroundOlder adults' health maintenance may be enhanced by having access to online health information. However, usability issues may prevent older adults from easily accessing such information. Prior research has shown that aging is associated with a unique pattern of cognitive changes, and knowledge of these changes may be used in the design of health websites for older adults. ObjectiveThe goal of the current study was to examine whether older adults use of a health information website was affected by an alternative information architecture and access interface (hierarchical versus tag-based). MethodsFifty younger adults (aged 18-23) and 50 older adults (aged 60-80) navigated a health information website, which was organized hierarchically or used tags/keywords, to find answers to health-related questions while their performance was tracked. We hypothesized that older adults would perform better in the tag-based health information website because it placed greater demands on abilities that remain intact with aging (verbal ability and vocabulary). ResultsThe pattern of age-related differences in computer use was consistent with prior research with older adults. We found that older adults had been using computers for less time (F1,98= 10.6, P= .002) and used them less often (F1,98= 11.3, P= .001) than younger adults. Also consistent with the cognitive aging literature, younger adults had greater spatial visualization and orientation abilities (F1,98= 34.6, P< .001 and F1,98= 6.8, P= .01) and a larger memory span (F1,98= 5.7, P= .02) than older adults, but older adults had greater vocabulary (F1,98= 11.4, P= .001). Older adults also took significantly more medications than younger adults (F1,98= 57.7, P< .001). In the information search task, older adults performed worse than younger adults (F1,96= 18.0, P< .001). However, there was a significant age × condition interaction indicating that while younger adults outperformed older adults in the hierarchical condition (F1,96= 25.2, P< .001), there were no significant age-related differences in the tag-based condition, indicating that older adults performed as well as younger adults in this condition. ConclusionsAccess to online health information is increasing in popularity and can lead to a more informed health consumer. However, usability barriers may differentially affect older adults. The results of the current study suggest that the design of health information websites that take into account age-related changes in cognition can enhance older adults' access to such information.